User innovation and the entrepreneurship phenomenon in the digital economy - Isaías, Pedro; Carvalho, Luísa Cagica 1970- (Advances in electronic commerce (AEC) book series, 2018)
"This book addresses the strategic business practice and the role of end-users' issues within the digital economy. It emphasizes emergent and innovative aspects of design, development and implementation of digital economy initiatives, highlighting the relationship and interaction between humans and the technologies they routinely use to operate and live in a digital economy"--